Uji Organoleptik Formulasi Biskuit Ikan Tuna sebagai Makanan Tambahan pada Balita Stunting - Sari Prihatin; Asni Annisa Siregar; Juhartini J; Warda W (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2024)
The processing of food materials to meet human nutritional needs can take various forms, including the production of biscuits. Nutrient sources derived from animal-based processed foods are considered superior compared to other sources of protein. Tuna stands out as an affordable animal protein source widely available in the community, enriched with essential nutrients such as omega-3, iron, magnesium, and more. The abundant nutritional content in tuna serves as the basis for conducting research on the formulation of complementary feeding (MP-ASI) in the form of tuna biscuits as an effort to prevent stunting. This research employs an experimental design involving the stages of creating tuna biscuit formulations and conducting organoleptic tests to determine the optimal biscuit formulation. Based on the results of the organoleptic test, tuna biscuits with formula 3 gave the most preferred taste, colour and aroma and texture to the panelists with a score of 15, followed by formula 2 with a score of 14 using the hedonic test formula.